How older adults use Ride-hailing booking technology in California. (January 2022) - Misra, Aditi; Shirgaokar, Manish; Weinstein Agrawal, Asha; Dobbs, Bonnie; Wachs, Martin
Highlights: Contrary to popular belief, many over 65 years ride-hail, often self-booking rides. Older adults who are more comfortable with technology book via the app. Those who are less comfortable with technology rely on others or use phone booking. Those with health issues and disabilities are more likely to book trips using an app. More seniors would likely use ride-hailing if the booking process is made easy for everyone. Abstract: Ride-hailing services like Lyft and Uber have the potential to improve mobility for many older adults, especially those who cannot or prefer not to drive. We used survey data from 2, 917 Californians 55 years and older to investigate (1) how older adults who currently ride-hail booked their trips, and (2) what personal characteristics, including attitudes towards technology, were correlated with booking trips online versus by phone or with help. We specified four binary probit models in which the outcome variables are the manner in which a respondent accessed ride-hailing services: self-booked by phone, self-booked by app, booked by a family/friend/caregiver but rode alone, or booked by others and rode with them. We controlled for two attitudinal constructs (confident and cautious about technology), residential location, general travel behavior, physical health, and standard socio-economic factors. We found that respondents who were more confident using technology booked via apps, while those who were more cautious about technology were less likely to book using apps. This latter group was more likely to book by phone or rely on others for help. Other characteristics associated with higher likelihood of booking via apps were: living in the suburbs, not relying on others for rides, having physical health issues, being college educated, and being non-Hispanic. Our findings provide a basis to think about expanding ride-hailing to other older adults, particularly those who are not comfortable with technology, through convenient access to ride-hailing booking.